Rileggendo vecchi dati. Spunti sull'Orientalizzante tarquiniese (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2009)
The analysis of the distribution of foreign objects, on the basis of the archaeological evidences (both published and unpublished), makes it possible to reconsider the role of Tarquinia during the Orientalizing period, focusing on the relationship with other Etruscan cities and the development in Tarquinia itself during the Archaic and Classical periods. In fact, besides funerary tumuli, showing the power of the aristoi, the spread inland of Near-Eastern aegyptiaca and Greek (in particular Corinthian) objects show an opening to Mediterranean relationships. This general setting makes it possible to assess the territorial organization pursued by the Tarquinian community in order to guarantee the abundant supply of these commercial trends. Another interesting sign of these Mediterranean contacts is the adoption in local ware tradition of foreign vase-shapes (e.g. pyxides, oinochoai, etc.), showing both new trends in the development of vase-shapes and the respect of the local religious tradition.